Cytotoxic Activity of Tegari (Dianella nemorosa Lam.) Methanol Extract Against HeLa Cells - Karim, Aditya Krishar; ., Sismindari; Asmara, Widya; ., Istriyati (Indonesian Journal of Biotechnology, 2012)
Dianella nemorosa Lam. also known as tegari belonging to the Liliaceae family. This plant has been utilized for Papua traditional medicine as well as anticancer agent. This research examined potential cytotoxic activity of tegari (D. nemorosa) leaves extract against cervical cancer cell line (HeLa). Methanol extract was obtained by extracting the leaves powder using methanol. Extract was then applied into HeLa cell line to find out the cytotoxic activity. MTT [3-(4,5-dimetilthiazol-2-il)2,5-difeniltetrazolium bromida) assay was used to measure the cytotoxic activity. The result indicated that D. nemorosa leaves extract possessed cytotoxic activity in HeLa cell line with IC50 values were 685,69 µg/ml, 506,43 µg/ml and 708 µg/ml at the incubation period of 24, 48 and 72 h respectively. The strongest cytotoxic was showed by methanol extract incubated in 48 h.